2013
DOI: 10.1080/13632469.2013.847874
|View full text |Cite
|
Sign up to set email alerts
|

Full-Scale Shaking Table Tests on a Substandard RC Building Repaired and Strengthened with Post-Tensioned Metal Straps

Abstract: The effectiveness of anovel Post-Tensioned Metal Strapping(PTMS)techniqueat enhancingthe seismic behaviourof asubstandard RC buildingwas investigated through full-scale shake-tabletests duringthe EU-fundedproject BANDIT.The building had inadequate reinforcement detailing in columns and joints toreplicateold construction practices.After thebarebuildingwas initially damagedsignificantly,itwas repairedand strengthened with PTMS to perform additionalseismic tests.The PTMS technique improvedconsiderablythe seismic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 38 publications
(28 reference statements)
0
25
0
Order By: Relevance
“…The steel straps used in these studies are recycled steel straps which are commonly used as packing strands for exporting good crates. The benefit of using steel straps as confining material, aside from its cost effectiveness, is it allows post-tensioning confining pressure around concrete which ensure fully effective use of the confining material [6][7][8]. As being reported previously, the passive type of confining materials which are activated by the dilation of the concrete, not reaching their ultimate strain at the ultimate failure.…”
Section: Introductionmentioning
confidence: 89%
“…The steel straps used in these studies are recycled steel straps which are commonly used as packing strands for exporting good crates. The benefit of using steel straps as confining material, aside from its cost effectiveness, is it allows post-tensioning confining pressure around concrete which ensure fully effective use of the confining material [6][7][8]. As being reported previously, the passive type of confining materials which are activated by the dilation of the concrete, not reaching their ultimate strain at the ultimate failure.…”
Section: Introductionmentioning
confidence: 89%
“…General geometry and reinforcement detailing of BANDIT building (units: mm), partially adapted from Garcia et al (2014a) The beams had a cross section of 260×400 mm in the X direction and 260×300 mm in the Y direction (see Post-tensioned bolts (CEN 2004a). The top beam reinforcement of the 1 st floor joints was anchored using 90° bends and U-shaped hooks, which provided adequate anchorage according to EC2 requirements.…”
Section: Figmentioning
confidence: 99%
“…Experimental research has confirmed the effectiveness of the PTMS technique at enhancing the capacity of columns under compression (Moghaddam et al 2010), beams with short lap-splices (Helal et al 2014) and substandard beam-column joints subjected to cyclic load (Helal 2012). More recently, the technique was proven extremely effective at enhancing the seismic behaviour of a full-scale PTMS-retrofitted RC building subjected to low and medium-intensity (up to PGA=0.35g) shake table tests (Garcia et al 2014a). However, the behaviour of PTMS-retrofitted structures subjected to severe shaking (PGA>0.40g) still needs to be investigated.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations